Pathogenetic therapy of multiple sclerosis - N. V. Komissarova; M. A. Urban; D. M. Gaysina; A. R. Gimazdinova; Ya. M. Perevozchikova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Multiple sclerosis is accompanied by rapid progression of the disease, the development of early disability and a violation of the patient's quality of life. In recent years, advances in understanding the etiology and pathogenesis of this disease have led to the expansion of therapeutic approaches, it has become possible to influence the course of the disease. Objective - to study the effectiveness of the use of drugs that change the course of multiple sclerosis in patients registered at the center of multiple sclerosis of the Udmurt Republic.Materials and methods. The statistical analysis was performed on 45 patients of the neurological department of the "First Republican Clinical Hospital" of the Ministry of Health of the Udmurt Republic, diagnosed with multiple sclerosis, using immunomodulatory or immunosuppressive therapy.Results. At the beginning of the study, the group of patients using immunomodulatory therapy included 31 patients (68.89 %), the group of immunosuppressors -14 patients (31.11 %). The average time from the onset of the disease to the start of therapy was 1.64 ± 5.71 months. 42 patients (93.33 %) out of 45 included in the study started therapy with an immunomodulator. The average time from the start of therapy to inclusion in the study was 113.00 ± 47.52 months in the immunomodulatory therapy group. 11 patients (78.57 %) out of 14 taking immunosuppressive therapy at the start of the study switched to it after previous immunomodulatory therapy. 3 patients (6.67 %) out of 45 included in the study started treatment with immunosuppressive therapy. In the immunosuppressive therapy group, the duration of treatment was 62.57 ± 74.52 months. Progression of the disease from the moment of initiation of therapy to inclusion in the study was observed in 19 patients - 42.22 %. An increase in the EDSS index was recorded by an average of 1.82 ± 0.31 points. Improvement of clinical condition was observed in 6 patients - 13.33 %. A decrease in the EDSS index was recorded by an average of 0.91 ± 0.22 points. The difference in the EDSS index in the groups of immunomodulators and immunosuppressors is insignificant. There was no dependence of the patient's clinical condition on the number and activity of foci of demyelination.Conclusions. The objective clinical condition of the patient has no significant difference in the groups of immunomodulatory and immunosuppressive therapy, which suggests that the correct selection of a particular drug by the attending physician and its constant use by the patient is important in order to reduce the risks of complications, slow down the progression of the disease and preserve the quality of life of the patient.